AB0610 Difference in Skin Elasticity between Diffuse and Limited Systemic Sclerosis. (10th June 2014) - Bruno, C.; Tripolino, C.; Mazzuca, S.; Calabria, M.; Ursini, F.; Naty, S.; Grembiale, R.D.
Abstract : Background: Systemic sclerosis (SSc) is a chronic autoimmune disease characterized by vascular damage and severe fibroproliferative phenotype, which affects skin and internal organs. To date, the modified Rodnan Skin Score (mRSS) is the most employed technique to assess cutaneous involvement in SSc. However, recent studies consider the employment of ultrasound elastosonography (UE), highlighting its ability to identify the reduction of strain in the skin. Currently, SSc can be classified into two different subsets: limited (LSS) and diffuse (DSS) disease. The former is usually confined to specific regions of the body, with no internal organ involvement, the latter is characterized by diffuse skin involvement, severe internal organ involvement and poor prognosis. Objectives: The present study was aimed to explore possible differences in skin stiffness between LSS and DSS by using UE. Methods: 20 SSc patients (10 with LSS and 10 with DSS) and 10 healthy subjects, were recruited for the present study. They underwent clinical examination and ultrasound evaluation. UE was performed at palmar surface of each finger tip. Images were obtained by applying repetitive skin compression. The elastogram, which reflects the relative elasticity of the tissues, was created as a color coded map (i.e. blue = great stiffness, red = low stiffness). Images were analyzed by a proprietary software (Esaote elastosonography module, Esaote, Inc., Italy) that allows to obtain a numeric evaluation of stiffness expressing the global percentage of hardness. "Skin stiffness" was computed by considering the average of eight fingers for each patient. Results: Table 1 reports clinical and ultrasound features of SSc group and control group. As shown, mean age was 61±14 years in SSc subjects and 55±13.9 years in healthy subjects. Overall, SSc subjects showed higher skin stiffness values than control group (p<0.01), whereas no difference concerning the other variables were found. Among SSc group, patients with LSS were comparable to DSS regarding age, disease duration and Raynaud's phenomenon duration, whereas mRSS was significantly lower (p=0.01). Regarding skin stiffness, DSS subjects showed highest values when compared to both controls (p<0.01) and LSS subjects (Fig. 1 ). Conclusions: The present investigation has two main results. First, ultrasound with elastosonography seem to discriminate skin stiffening in SSc patients compared to healthy subjects, thus confirming the findings of previous investigations. Second, among SSc patients, those with DSS show a higher skin stiffness compared to LSS subjects, supporting the more severe course of DSS compared to LSS. References: Iagnocco A et al (2010) J Rheumatol 37: 1688-91 Ostojić P et al (2006) Clin Rheumatol 25:453-7 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1280